the formulation of the basil (Ocimum Basilicum Linn) leaf juiced ointment as a liniment - iim hasanah (AKADEMI FARMASI JEMBER, 2022)
Basil is traditional medicinal plants found a lot of in Indonesia. Basil leaves affication as analgetic, antiinflamantory, bacteria and antioxidant. This study aims to make an ointment stock that fulfills the requirements of preparation, knowing the physical properties of basil (Ocimum sanctum L) leaf juice. This research is an experimental research by making and evaluating basil leaves ointment preparations. The result of this research is that the juice of basil leaves (Ocimum sanctum L) containing the flavanoid compounds, tannins, and steroids and can be made as ointment stock that fulfill the requirements of physical properties evaluation. The organoleptic test included color, odor, and texture, from the three bases, it showed that the different types of basil leaf-squeezed ointment bases caused differences in the strength of the ointment preparations, while the color showed clear white and green. In the pH test, the three preparations had a pH of 5, the pH met the requirements for the pH of the topical preparation, which is between 4 – 6 which is the same as the normal pH of the skin. The homogeneity test of the three preparations showed that the preparations were homogeneous (no coarse lumps). The dispersion test has a dispersion of FI 3,5 cm, FII 5 cm, FIII 5,2 cm. Meanwhile the adhesion test is 4 seconds, 4,30 seconds, and 4,50 seconds. Keywords : Basil leaves, Evaluation tests, Ointments